LANGUAGE VARIATIONS USED AT NONFORMAL EDUCATION (A SOSIOLINGUISTIC RESEARCH AT PONDOK PESANTREN) - Sari, Kharisma Puspita (VISION, 2014)
ABSTRACT This study aims to investigate language variations that are used by the teacher and the students in the noformal education namely madrasah diniyah at pondok pesantren. The researcher designed this study as explanative qualitative study. There are three steps in conducting this study. The first step is to collect the data. The researcher uses recording technique to collect the data. The interactive languages namely conversation among the teacher and the students in madrasah diniyah are regarded as the primary data. The researcher chooses data purposively. The second step is to analyze the data. The language variations theory from Chaer & Agustina is considered as the most appropriate theory for analyzing the data. The last step is to present the result of analysis. The researcher found the language variations as follows: (a) sosiolect or social dialect, (b) register, (c) casual language, and (d) spoken language. Keyword: Â Â  Language variation, sosiolinguistic research, madrasah diniyah, pondok pesantren